Evaluasi Hukum dan Tantangan Hak Perlindungan Konsumen di Indonesia: Refleksi Masa Lalu Saat Ini dan Yang Akan Datang - Putri, Resika Triani; Indriyani, Frisca; Kamila, Dinda Amalia; Imawan, Moh Dafiz (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
Legal evaluation and challenges of consumer protection rights in Indonesia are crucial issues in the context of economic development and globalization. In this study, the author examines existing regulations, including the Consumer Protection Law, and their implementation in practice. Reflection on the past shows weaknesses in law enforcement that often benefit producers rather than consumers. Currently, the challenges are increasingly complex with the presence of digital technology that creates new space for transactions, but also new risks for consumers. In the future, a more comprehensive strategy is needed, including increasing consumer awareness, strengthening consumer protection institutions, and adapting regulations to market dynamics. Thus, this evaluation aims to provide recommendations that can strengthen consumer protection rights and create a fairer business climate in Indonesia. Keywords : Law, Consumer Protection Rights